Single Angio-Seal™ Device as a Simplified and Technically Feasible Alternative for Tract Closure in Percutaneous Portal Vein Access: A Retrospective Study - Ismail Karluka; Mustafa Mazıcan (Diagnostics)
Purpose: This study aimed to evaluate the efficacy and safety of the Angio-Seal™ VIP vascular closure device (VCD) in achieving hemostasis following percutaneous transhepatic portal venous interventions. Methods: This retrospective study evaluated 20 patients (mean age: 52.85 ± 16.18 years; 80% male) who underwent percutaneous transhepatic portal vein interventions followed by tract closure with the Angio-Seal™ device between January 2016 and September 2024. Procedural data, pre- and post-procedural hemoglobin and hematocrit levels, and complications were analyzed. Technical success was defined as the successful deployment of the device with immediate hemostasis and no evidence of bleeding on post-procedural imaging. Results: Technical success, as defined in this study, was achieved in all 20 procedures (100%). The mean hemoglobin level declined from 11.91 ± 2.01 g/dL to 11.09 ± 2.19 g/dL (p < 0.001), and the mean hematocrit level decreased from 36.18 ± 6.03% to 32.98 ± 5.80% (p = 0.001). A hemoglobin drop ≥2 g/dL occurred in two patients (10%) and a hematocrit drop ≥4% in six patients (30%); none were associated with imaging or clinical evidence of hemorrhage. No major complications were observed. Minor complications, including localized pain managed with analgesics, occurred in five patients (25%). Follow-up imaging confirmed the absence of hemoperitoneum or device-related failure. Conclusions: Angio-Seal™ is a technically feasible, safe, and effective option for tract closure following percutaneous transhepatic portal vein access. This single-device approach may offer a cost-effective alternative to traditional embolization techniques. However, more extensive prospective studies are required to validate these findings.